The impact of employee work perceptions on purchase intentions from a company store. Issue 5 (15th August 2016) - Bodkin, Charles D.; Peters, Cara; Thomas, Jane
Abstract : Purpose: Company stores market to their internal employees via the distribution of branded promotional products. The purpose of this study is to investigate factors that may influence when an employee is more likely to purchase from a company store. Design/methodology/approach: A survey was administered to the members of a chamber of commerce located in the southeastern USA. Data were analyzed using regression, and post hoc analyses were conducted using an analysis of covariance. Findings: Organizational identification and job satisfaction significantly impacted employees' intentions to purchase from a company store. Gender, education, marital status and years of work experience were personal factors that moderated that relationship. Firm size and employee rank were company factors that moderated the relationship between employee work perceptions and employee purchase intentions at a company store. Originality/value: No research to date exists on company stores. This study is unique in that it proposes internal branding as a theoretical foundation for understanding company stores and examines factors that impact employees' intentions to purchase from a company store.